A framework for the corporate governance of data – theoretical background and empirical evidence - Dahlberg, Tomi; Nokkala, Tiina (Business, Management and Economics Engineering, 2015)
In a modern organization, IT and digital data have transformed from being functional resources to integral elements of business strategy. Against this background, our article addresses corporate governance of digital data in general and that of aging societies in particular. To describe the role of executives and managers in data governance, we first review the corporate and IT governance literature. We then propose a theoretical framework for the governance of data: a novel construct. We apply the framework to the governance of aging societies related data, that is, to answer the question of how best to manage the provision of services to citizens with digital data enablement and support. We also disclose the results from two recent surveys, with 212 and 68 respondents respectively, on the business significance of data governance. The survey results reveal that good governance of data is considered critical to organizations. As concluding remarks, we discuss the significance of our results, our contributions to research, the limitations of our study and its managerial implications.